Word-learning performance of children with and without cochlear implants given synchronous and asynchronous cues. (3rd October 2017) - Lund, Emily; Schuele, C. Melanie
ABSTRACT: This study sought to evaluate the effects of synchronous and asynchronous auditory–visual cues on the word-learning performance of children with cochlear implants and children with normal hearing matched for chronological age. Children with cochlear implants (n = 9) who had worn the implant for less than one year and children matched for chronological age ( n = 9) participated in rapid word-learning trials. Children with cochlear implants did not learn words in either the synchronous or asynchronous condition (U = 49.5, p = .99; d = 0.05). Children with normal hearing learned more words in the synchronous rather than asynchronous condition (U = 78.5, p = .04; d = 0.95). These findings represent a first step toward determining how task-level factors influence the lexical outcomes of children with cochlear implants.